Understanding structural conservation through materials science: strategies and didactics - Laura Fuster-López; Cecil Krarup Andersen (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Mechanical properties and the structure of materials are key elements in understanding how structural interventions in conservation treatments affect cultural heritage objects. In this context, engineering mechanics can help determine the strength and stability found in art objects as it can provide both explanation and prediction of failure in materials. It has therefore shown to be an effective method for developing useful solutions to conservation problems. Since materials science and mechanics can help conservators predict the long term consequences of their treatments and provide them with tools to avoid future problems, it should be present in all conservation-restoration training programs to help promote students’ understanding of the degradation mechanisms in cultural materials (and their correlation with chemical and biological degradation) as well as the implications behind conservation treatments.